2015
DOI: 10.1186/s13072-015-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Wanderer, an interactive viewer to explore DNA methylation and gene expression data in human cancer

Abstract: BackgroundThe Cancer Genome Atlas (TCGA) offers a multilayered view of genomics and epigenomics data of many human cancer types. However, the retrieval of expression and methylation data from TCGA is a cumbersome and time-consuming task.ResultsWanderer is an intuitive Web tool allowing real time access and visualization of gene expression and DNA methylation profiles from TCGA. Given a gene query and selection of a TCGA dataset (e.g., colon adenocarcinomas), the Web resource provides the expression profile, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 15 publications
5
163
0
Order By: Relevance
“…To analyze TCGA data, we have used the Wanderer application that we had developed for this purpose and that is described in detail elsewhere (24). The analysis of expression microarray data for specific genes of interest was performed essentially as previously described (20).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze TCGA data, we have used the Wanderer application that we had developed for this purpose and that is described in detail elsewhere (24). The analysis of expression microarray data for specific genes of interest was performed essentially as previously described (20).…”
Section: Resultsmentioning
confidence: 99%
“…Although single CpG methylation patterns might be a potential biomarker for cancer risk assessment [35], it has also been suggested that different genomic regions can be associated with differential survival prognosis [36]. Moreover, several recently published web tools emphasize the need for analyzing DNA methylation data based on sub-regions [9,10]. Therefore, we provide the users with a detailed overview of individual CpG sites with the options to select genomic regions (relative to CGI and gene sub-region), methods to establish cut-off points for dichotomizing higher and lower methylation patient groups (mean, median, lower quantile, upper quantile and maxstat) and adjustment type.…”
Section: Construction Of the Web Toolmentioning
confidence: 99%
“…However, analyzing the raw data from such consortia is a labor-intensive and time-consuming process that requires specific bioinformatics skills. Multiple public resources such as Wanderer [9], METHHC [10] and MEXPRESS [11] provide a simple user interface to explore the relationship between methylation and gene expression data originating from TCGA. Additionally, tools to perform survival analysis using gene expression data from TCGA are also available to the research community [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the involvement this epigenetic mechanism of silencing for FENDRR and FOXF1, firstly we analyzed the in silico results from The Cancer Genome Atlas database [17] using the Wanderer web tool [18]. The methylation status of the promoter CpG islands of FENDRR and FOXF1 was significantly different in tumor versus normal tissue.…”
Section: Methylation Status Of Fendrr and Foxf1mentioning
confidence: 99%